Scheduled Tribes in Baghelkhand Region: Population Growth and Distribution - Singh, Ravi S.; Kharwar, Rakesh Kumar (National Geographical Journal of India, 2022)
The scheduled tribes (STs) constitute a major section of the Indian society. They represent a wide variety of population elements in terms of socio-economic and cultural characteristics as well as levels of development. The STs’ population distribution and population growth has been changing continuously. According to the 2011census, Baghelkhand region had about 3.90 percent ST population of India and it contributes 32.87 percent to the total population (16.58 % male and 16.29% female) of the region. Keeping this fact in view, an attempt has been made in the present paper to study the growth of population and changing pattern of spatial distribution of the STs in Baghelkhand region. The study is based mainly on secondary data collected from District Census Handbook and other governmental and non-governmental publications. The analyses reveal that dense forests and hilly areas in this region play important role in the distribution pattern of ST population which varies noticeably. A very high concentration of ST population is in southeast and southwest part of Bundelkhand